WATER CONSERVATION IN SUGAR INDUSTRY: A CASE STUDY OF LOKMANGAL SUGAR, ETHANOL AND CO-GENERATION INDUSTRIES LTD, BHANDARKAVATHE - DESHMUKH G. K.; SONAJE N. P. (International Journal of Innovations in Engineering Research and Technology, 2021)
Sugar manufacturing process requires considerably a large amount of water. Wastewater generated also is huge. Reducing the water consumption for industrial process is challenging task. Conservation of this resource is significant in the aspect of environmental and economical sustainability.Water conservation is possible by implementing the optimum water utilization techniques. Excess condensate water generated from the process can used back in the process, reducing the cold water required for the cooling & other purpose. This excess condensate water can also be used for Turbine cooling towers as make up. A Case Study of Lokmangal SugarEthanol andCo-Generation Industries Ltd, Bhandarkavathe reveals that the excesscondensate water available during the process of sugar manufacturing is equivalent to 216.36 m3/day and it showsthat judiciaous use of water and application of 3 R concept in sugar industry,insteadof bringing water from outside source water will be available from industry.